The Brilliance of the Iranian Journal of Archaeological Studies (IJAS) in the International and National Arena - Mehdi Mortazavi (Iranian Journal of Archaeological Studies)
Volume 14, Issue 2, 2024I am delighted and honoured to present this issue of the Iranian Journal of Archaeological Studies to you, our esteemed readers. In this note, I will introduce the valuable achievements and diverse articles of this issue.